Development of photodynamic therapy in treating oral diseases - Wang, Ling; Chen, Qiang; Liu, Dan (Frontiers in Oral Health, 2025)
The morbidity of oral disorders, including gingivitis, caries, endodontic-periodontal diseases, and oral cancer, is relatively high globally. Pathogenic cells are the root cause of many oral disorders, and oral therapies depend on eradicating them. Photodynamic therapy (PDT) has been established as a potential and non-invasive local adjuvant treatment for oral disorders. PDT consists of three essential components: photosensitizer (PS), a light source with a certain wavelength, and oxygen dissolved in the cells. These three components can interact to cause damage to proteins, lipids, nucleic acids, and other biological components within diseased tissues. Herein, we aimed to provide a detailed understanding of PDT and how it can treat oral diseases. Concerns about PDT and potential remedies are also a factor. PDT has been shown in numerous clinical studies to be an efficient supplementary therapy that can reduce pathogenic cells. The PDT has great potential for dental applications, including treating bacterial and fungal infections during root canal therapy and preventing oral cancer, potentially malignant disorders, periodontitis, dental caries, and peri-implant disorders. Although PDT has been promoted as having significant potential and utility in dentistry, more clinical research must be conducted before being used broadly.